ADHD PADA ANAK DENGAN RETARDASI MENTAL - Nathania Bayu Astrella (Ilmu Psikologi Universitas Yudharta Pasuruan)
The diagnosis of mental retardation with ADHD in children, statistically record 8% - 39%. Children with mental retardation, requires certain ways to maximize their potential and quality of life. The condition ADHD are likely brought certain challenges to the handling of these children. This article presents the description of mentally retarded children with ADHD in their natural setting, school and home. It’s a qualitative research, descriptive case study, with holistic multi-case design. Purposive sampling technique found two (2) children as research subjects. Pattern matching technique is used for data analysis. The result of this study shows challenges for school teacher while working with mentally retarded with ADHD children. Accommodate their ADHD in positive and productive activities, are likely helps the handling of their mental retardation condition